2013
DOI: 10.1089/sur.2011.097
|View full text |Cite
|
Sign up to set email alerts
|

Use of Silver in the Prevention and Treatment of Infections: Silver Review

Abstract: Background: The use of silver for the treatment of various maladies or to prevent the transmission of infection dates back to at least 4000 b.c.e. Medical applications are documented in the literature throughout the 17th and 18th centuries. The bactericidal activity of silver is well established. Silver nitrate was used topically throughout the 1800s for the treatment of burns, ulcerations, and infected wounds, and although its use declined after World War II and the advent of antibiotics, Fox revitalized its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
103
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(105 citation statements)
references
References 176 publications
0
103
0
2
Order By: Relevance
“…Furthermore, re- sistance against commonly used antibiotics has globally emerged in recent years. New antimicrobial coatings of implant surfaces may therefore be an attractive option to reduce the risk and improve the treatment of IAIs (19,39). Little is known about the efficacy of silver against biofilm-forming staphylococci in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, re- sistance against commonly used antibiotics has globally emerged in recent years. New antimicrobial coatings of implant surfaces may therefore be an attractive option to reduce the risk and improve the treatment of IAIs (19,39). Little is known about the efficacy of silver against biofilm-forming staphylococci in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 However, there is limited research on Ag-loaded antibacterial coatings for biomedical materials and the majority of research has been focused on Correspondence to: X. Jiang; e-mail: anhong2225@163.com. modified or composited antibacterial materials, which have rarely been shown to be flexible or biocompatible.…”
Section: Introductionmentioning
confidence: 99%
“…5,[7][8][9] The use of silver for treatment and preventive purposes of infection dates back to at least 4000 BC due its antimicrobial and bactericidal activities. 10 Khare et al have found that the rate of colonization at silverimpregnated catheter tip was lower than stander catheter, specifically, a lower rate of colonization of coagulase negative staphylococci on the other hand the effect on CR-BSI was not statistically significant.…”
Section: Introductionmentioning
confidence: 99%